Latent Factors in Attention Emerge from 9 Years of Age among Elementary School Children - Tao, Ting; Wang, Ligang; Fan, Chunlei; Gao, Wenbin; Shi, Jiannong (Frontiers in Psychology, 2017)
We explored the development of attention among elementary school children. Three hundred sixty-five primary school children aged 7–12 years completed seven attention tests (alertness, focused attention, divided attention, attentional switching, sustained attention, spatial attention, and supervisory attention). A factor analysis indicated that there was no stable construct of attention among 7- to 8-year-old children. However, from 9 years on, children’s attention could be separated into perceptual and executive attention. Notably, however, the attention types included in these two factors differed from those among adults.